2016
DOI: 10.2500/ajra.2016.30.4273
|View full text |Cite
|
Sign up to set email alerts
|

Bleeding Risk Associated with Resection of the Middle Turbinate during Functional Endoscopic Sinus Surgery

Abstract: There was no increased risk of major bleeding or other complication associated with resection of the MT. However, there was a significantly increased minor bleeding rate associated with MT resection, particularly if the patient was on anticoagulants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 14 publications
0
10
0
1
Order By: Relevance
“…Of note, they did not specify the site of bleeding, so it was possible the epistaxis could have occurred from a site remote from the MT. 22 The current study compared favorably with Miller et al., with a 0% incidence of postoperative epistaxis requiring operative intervention.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Of note, they did not specify the site of bleeding, so it was possible the epistaxis could have occurred from a site remote from the MT. 22 The current study compared favorably with Miller et al., with a 0% incidence of postoperative epistaxis requiring operative intervention.…”
Section: Discussionmentioning
confidence: 65%
“…Despite studies showing benefits of MTR during ESS for CRSwNP, many surgeons still avoid MTR due to concerns of postoperative epistaxis, cerebrospinal fluid (CSF) leak, frontal outflow stenosis, or empty nose syndrome (ENS). 22,23 Studies have shown mixed incidences or concerns regarding the aforementioned complications as they relate to MTR. 14,2426 The purpose of this study was to assess the safety of MTR during ESS by determining the incidences of 3 of the most significant complications associated with MTR: intraoperative CSF leak, postoperative epistaxis requiring operative intervention, and postoperative complete frontal stenosis.…”
Section: Introductionmentioning
confidence: 99%
“…Postoperative bleeding has been considered a risk of resection, predominantly minor mucosal oozing or from feeding arterial vessels . The MT takes its vascular supply from a rich anastomosis of vessels based predominantly on the sphenopalatine, anterior, and posterior ethmoid arteries .…”
Section: Discussionmentioning
confidence: 99%
“…Early proponents of ESS argued that the MT should be preserved, citing the risks of alteration in nasal function including humidification and airflow, deterioration in sense of smell, destruction of intraoperative landmarks, iatrogenic frontal sinusitis, postoperative bleeding, and the risk of developing atrophic rhinitis, or empty nose syndrome (ENS) . More recent studies have provided evidence that these concerns are unfounded; however, ongoing debate exists.…”
mentioning
confidence: 99%
“…These data may add a new arm to standard postoperative care regiments. Miller et al 12 review data that analyzes the impact of middle turbinate resection on bleeding after ESS and conclude that there is no change in major bleeding risk but that patients on anticoagulants are at an increased risk of minor bleeds after surgery. Rosen et al 13 conducted a systematic review of antibiotic use in endoscopic skull base surgery and show that, in general, meningitis is exceedingly rare in endoscopic relative to open procedures.…”
mentioning
confidence: 99%